2005
DOI: 10.1159/000086410
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylhomocysteine Metabolism in Different Cell Lines: Effect of Hypoxia and Cell Density

Abstract: Background/Aims: The methylation potential (MP) is defined as the ratio of S-adenosylmethionine (AdoMet) to S-adenosylhomocysteine (AdoHcy). It was shown recently that hypoxia increases AdoMet/AdoHcy ratio in HepG2 cells (Hermes et al., Exp Cell Res 294: 325-334, 2004). In the present study, we compared AdoMet/AdoHcy ratio and energy metabolism in HepG2, HEK-293, HeLa, MCF-7 and SK-HEP-1 cell lines under normoxia and hypoxia. Methods: Metabolite concentrations were measured by HPLC. In addition, AdoHcy hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
4
13
0
Order By: Relevance
“…However, Hermes and colleagues (32) observed that hypoxia leads to increased SAM and decreased SAH levels in HepG2 cells. This difference may be due to alterations in the cell density of cultured cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, Hermes and colleagues (32) observed that hypoxia leads to increased SAM and decreased SAH levels in HepG2 cells. This difference may be due to alterations in the cell density of cultured cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Since it was previously shown that hypoxia decreases AdoHcy-hydrolase expression in HepG2 cells [5,31] we also examined in this study the effect of hypoxia on the AdoHcy-hydrolase mRNA content in rat kidneys. CO exposure decreased the mRNA content of AdoHcy-hydrolase in the rat kidney by 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to all other experiments cells were rinsed with PBS and then cultured with serumfree MEM for 24 h. This allows us to compare our results to previous studies [3,10,21].…”
Section: Construction Of Adohcyase Overproducing Plasmid (Pcdnacd20)mentioning
confidence: 99%
“…Therefore, the aim of the present study was to evaluate whether elevated AdoHcyase activity might also lead to changes in AdoHcy metabolism and thus, influence energy metabolism, cell viability, growth rate, and DNA methylation. As a model system, we used HEK-293 cells stably overexpressing AdoHcyase to different extents, because HEK-293 cells exhibit high intracellular AdoHcy levels and a low AdoMet/AdoHcy ratio compared to other established cell lines [21].…”
Section: Introductionmentioning
confidence: 99%